Sergei Yesenin’s death – a suicide or a murder staged to look like a suicide? An analysis of some selected circumstances of the death and injuries - Arkuszewski, Piotr; Antoszczyk, Łukasz; Mazurek-Wardak, Magdalena; Wardak, Zbigniew (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article contains some consideration about selected, crucial circumstances of the death of the Russian poet Sergei Yesenin and it also concerns the injuries found in him during the post-mortem examination. The authors have focused on the most important and currently available information which indicates that the true cause of the poet’s death might have been different from the official cause of death. Some facts discredit suicidal hanging and the others suggest a possibility of a murder staged to look like a suicide.